Metagenomic analysis reveals viral diversity in the viromes of wild and cultivated blueberry (V. corymbosum) in Florida - Saad, Norsazilawati; Harmon, Philip F.; Polston, Jane Elizabeth; Varsani, Arvind; Alcala-Briseno, Ricardo Ivan; Olmstead, James W. (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Viral metagenomics has allowed the detection of novel ssDNA viruses in various environments, hence revealing the widespread nature of these viruses. Since the taxonomically approved virus species of the ssDNA group are composed of circular genomes, these viruses can therefore be enriched by rolling circle amplification (RCA) in the sample preparation step prior to the construction of DNA libraries. A metagenomic approach using DNA extracted from wild and cultivated Vaccinium corymbosum through the enrichment of virus like particles followed by RCA was carried out to characterize and describe viral diversity in V. corymbosum. Sequencing was performed on Illumina HiSeq 2500 platform to generate plant viromes and analyzed using a metagenome analysis pipeline. Analysis of the wild and cultivated plant viromes revealed the diversity of DNA viruses as well as the discovery of known and potentially novel viruses in these plants. De novo assembled scaffolds generated from the viromes produced sequences with homologies to plant virus species from fifteen genera in the family Geminiviridae, representing a complete set of novel viruses that are highly divergent to the current taxonomically recognized species. A common virus known to infect commercial blueberries, Blueberry red ringspot virus (BRRV), was identified for the first time in wild species of V. corymbosum in this study. In addition, two de novo assembled viral genome has been discovered in wild V. corymbosum, possibly representing putative novel virus species in the family Geminiviridae, although further validation is required to determine the presence of these putative novel viruses due to the widespread nature of circular replication-associated protein-encoding ssDNA (CRESS-DNA) viruses.